Kelas MASK: Posbindu (integrated health post) revitalization as preventive action towards non-communicable disease during COVID-19 pandemic - Huriyati, Emy; Wahab, Abdul; Farmawati, Arta; Nisa, Ainun; Nurahma, Bira Arumndari (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Non-communicable diseases (NCDs) are not only caused by genetic factors, but it can also be due to behavioral factors, such as low physical activity, unhealthy diet, and lack of knowledge on nutrition and healthy lifestyle. An integrated health post (“pos pembinaan terpadu” abbreviated as posbindu) is a community-based program in Indonesia which aims to reduce the incidence of NCDs by promoting a healthy lifestyle and conducting monthly health screening. However, since the recruitment of the post’s cadres is voluntary, most of them do not have formal education on health and may not be familiar with health screening tools. Thus, improving their knowledge and skills on this subject is critical.Methods: The Kelas MASK project aimed to increase the knowledge and skills of posbindu cadres, especially on the risk, prevention, and basic screening tools for NCDs. The projects consisted of lecture, demonstrations, dan practices. The knowledge and skills on anthropometric measurements, blood pressure and simple biochemical analysis were evaluated based on the score obtained from the pre- and post- tests. Results: The Kelas MASK project increased the cadres’ knowledge, shown by the increase of the average post-test score compared to the pre-test score (increased by 4.03, p-value = 0.0000).Conclusion: All in all, the Kelas MASK project significantly increased the knowledge and skills of posbindu cadres on the prevention of NCDs.